Evaluasi Keberhasilan dalam Menjaga Konservasi Penebaran Beberapa Jenis Ikan di Waduk Penjalin, Jawa Tengah - Hendrawan Andika Luky Setiyo; Abdul Ghofar; Didik Wahju Hendro Tjahjo (Dinamika Lingkungan Indonesia, 2023)
Fish stocking is one efforts to optimize fish production. 137,000 fish including tilapia, silver barb, common carp and giant prawns were stocked in the Penjalin Reservoir. This study aims to evaluate the distribution of several types of fish in the Penjalin Reservoir including the ability to utilize feed and space resources, fish growth and the chances of being caught by fishermen. The method used is stratified random sampling. The research was conducted from December 2021 to February 2022 at 4 observation stations. Sampling of fish using gill nets with a mesh of 0.75; 1; 1.5; 2; 2.5 and 3 inches. In addition, data collection is assisted by enumerators. The results showed that the growth pattern of tilapia anf giant prawn is allometric negative, allometric positive for silver barb and common carp are isometric. Growth performance of stocked fish slow. Condition faktors for tilapia ranged from 0.78-1.45, silver barb 0.94-1.18, common carp 0.81-1.23 and giant prawns 0.75-1.14. Food habits analysis showed that the main food of tilapia is phytoplankton (99.9%), Silver barb is phytoplankton (90%), common carp is plants (85.71%) and giant prawns is mollusks (86.21%). Silver barb has a highest chance of getting caught by fishermen than the other fish.